PTU-096 Introduction of a gastroenterology outreach service and its impact within a tertiary university hospital. (June 2019) - Keen, Timothy; Rahman, Imdadur; Boger, Philip; Coleman, Nicholas; Stacey, Bernard
Abstract : Introduction: Hospital services are under increasing pressure which has led to an increased drive for earlier discharges. Various initiatives have begun to manage this. Within a UK tertiary hospital, a gastroenterology outreach team was formed from a pre-existing inpatient team alongside 2 remaining inpatient gastroenterology teams. This change coincided with the introduction of a new IT system with electronic triages and referrals. The aim of this service evaluation was to assess the impact on patient management, hospital stay and referring specialty satisfaction. Methods: The outreach team consisted of a consultant gastroenterologist and either a nurse specialist or junior doctor. The role of the outreach team was to review direct to gastroenterology triages within an acute medical admissions unit as well as all ward referrals. The direct to speciality triages were managed on the acute medical unit by the outreach team or admitted to a ward to be cared for by one of the inpatient teams. A retrospective analysis of a prospective kept database of all speciality triages and referrals was performed over a 15 month period from October 2017 to January 2019. Results: A mean increase of 15% per year in the number of direct to speciality triages and referrals was noted (mean 86/month). 49% of referrals were from 3 specialities; cardiology (25%), surgery (12%) and respiratory (12%). 100% of referrals and speciality triages were seen within 24 hrs. Vomiting and/or dysphagia (33%), diarrhoea (16%), GI bleeding (14%) and weight loss (12%) account for the majority of speciality triages (mean 68/month). The outreach team managed 22% of these without input from any inpatient teams. Following the introduction of the outreach team there has been a 14% reduction in the number of patients admitted to a ward from the acute medical unit (67% to 53%), an 11% increase in patients discharged <48 hours (34% to 45%) and a reduced length of hospital stay by 2 days (median of 4 to 2 days). A 1632 bed days saved per year equated to a cost saving of £652800 annually. Inpatient teams rated the outreach team as 9.2/10 overall and at 8.7/10 for patient management (1=poor, 10=excellent). Conclusions: The outreach team has been successful in improving initial patient management which has subsequently reduced the number of speciality triages admitted to a ward, increased patient discharges <48 hours, reduced length of stay, saved bed days and increased satisfaction with the service. We believe if this model of patient care was introduced to other hospitals it will have similar benefits.